Dietary patterns are associated with metabolic risk factors in South Asians living in the United States - Gadgil, Meghana D; Anderson, Cheryl A M; Kandula, Namratha R; Kanaya, Alka M (The Journal of nutrition, 2015)
South Asians are at high risk of metabolic syndrome, and dietary patterns may influence this risk. We aimed to determine prevalent dietary patterns for South Asians in the United States and their associations with risk factors for metabolic syndrome. South Asians aged 40-84 y without known cardiovascular disease were enrolled in a community-based cohort called Mediators of Atherosclerosis in South Asians Living in America. A validated food frequency questionnaire and serum samples for fasting and 2-h glucose, insulin, glycated hemoglobin, triglycerides, and total and HDL cholesterol were collected cross-sectionally. We used principal component analysis with varimax rotation to determine dietary patterns, and sequential linear and logistic regression models for associations with metabolic factors. A total of 892 participants were included (47% women). We identified 3 major dietary patterns: animal protein; fried snacks, sweets, and high-fat dairy; and fruits, vegetables, nuts, and legumes. These were analyzed by tertile of factor score. The highest vs. the lowest tertile of the fried snacks, sweets, and high-fat dairy pattern was associated with higher homeostasis model assessment of insulin resistance (HOMA-IR) (β: 1.88 mmol/L ⋅ uIU/L) and lower HDL cholesterol (β: -4.48 mg/dL) in a model adjusted for age, sex, study site, and caloric intake (P < 0.05). The animal protein pattern was associated with higher body mass index (β: 0.73 m/kg(2)), waist circumference (β: 0.84 cm), total cholesterol (β: 8.16 mg/dL), and LDL cholesterol (β: 5.69 mg/dL) (all P < 0.05). The fruits, vegetables, nuts, and legumes pattern was associated with lower odds of hypertension (OR: 0.63) and metabolic syndrome (OR: 0.53), and lower HOMA-IR (β: 1.95 mmol/L ⋅ uIU/L) (P < 0.05). The animal protein and the fried snacks, sweets, and high-fat dairy patterns were associated with adverse metabolic risk factors in South Asians in the United States, whereas the fruits, vegetables, nuts, and legumes pattern was linked with a decreased prevalence of hypertension and metabolic syndrome.